ADCP data of ice-covered and open-channel (macro-turbulent) flow, Pulmanki River, 2016-2020 - Lotsari, Eliisa Selina; Alho, Petteri; Kämäri, Maria; Kasvi, Elina (Zenodo, 2020)
README of ADCP_data_Lotsari_et_al_Water_opened.zip The ADCP data was the basis of the following paper: Macro-turbulent flow and its impacts on sediment transport potential of a subarctic river during ice-covered and open-channel conditions Eliisa Lotsari (1, 2), Michael Dietze (3), Maria Kämäri (4), Petteri Alho (2,5), Elina Kasvi (6,2) 1 Department of Geographical and Historical Studies, University of Eastern Finland, Yliopistokatu 2, P.O. Box 111, FI-80101, Joensuu, Finland. eliisa.lotsari@uef.fi 2 Department of Geography and Geology, University of Turku, FI-20014 Turun yliopisto, Turku, Finland. 3 Section 4.6 Geomorphology, German Research Centre for Geosciences GFZ Potsdam, D-14473 Potsdam, Germany. mdietze@gfz-potsdam.de 4 Finnish Environment Institute, Latokartanonkaari 11, FI-00790 Helsinki, Finland. maria.kamari@ymparisto.fi 5 Finnish Geospatial Research Institute, National Land Survey of Finland, Geodeetinrinne 2, FI-02430, Masala, Finland. mipeal@utu.fi 6 Turku University of Applied Sciences, Joukahaisenkatu 3, FI-20520, Turku, Finland. elina.kasvi@turkuamk.fi (Note: During the time of data gathering, Maria Kämäri worked at the University of Eastern Finland, and Elina Kasvi at the University of Turku) The data set has been measured with Sontek M9 or S5 sensors, depending on the time step (Table 1). Table 1. The measurement times, their acronyms (applied in the above mentioned publication) and applied sensors. In the acronyms of the measurement times W=winter low flow period, S=spring (snow-melt flood period), A=autumn low flow period. These information are presented also in the Table 1 of the above-mentioned publication. Date Acronym Sensor 17.2.2016 W2016M9 25.5.2016 S2016S5 10.9.2016 A2016M9 16.2.2017 W2017M9 31.5.2017 S2017M9 9.9.2017 A2017M9 9.2.2018 W2018M9 23.5.2018 S2018S5 8.9.2018 A2018S5 8.2.2019 W2019M9 21.5.2019 S2019M9 6.2.2020 W2020M9 RiverSurveyor Live software, and its most recent version, was used each time. The measurements have been done at Pulmanki River (69°55'59.09" N; 28° 2'34.32" ...